Enhanced performance for aggressive environments of green concrete composites reinforced with waste carpet fibers and palm oil fuel ash. (1st June 2018) - Mohammadhosseini, Hossein; Tahir, Mahmood Md.; Mohd Sam, Abdul Rahman; Abdul Shukor Lim, Nor Hasanah; Samadi, Mostafa
Abstract: World fiber production used in textile and carpet industries has been steadily increasing in the past few decades, now exceeding 70 million tons per year. About 50 tons of industrial waste polypropylene carpet fibers are sent to landfill in Malaysia annually. However, the landfill option is becoming increasingly impractical owing to growing landfill costs and the physical limitations on the number of landfill sites available. The need to recycle this waste is increasing owing to the lack of existing landfill spaces in many parts of the world, environmental concerns, and resource conservation. In this study, the performance of concrete composites comprising waste polypropylene (PP) carpet fiber and palm oil fuel ash (POFA) exposed to sulfate and acid after one year were investigated and obtained results were compared with those of water-cured specimens. Properties studied included visual inspection, mass, and strength measurements of hardened concrete. The particles morphology, as well as the effect of PP and POFA in the concrete-filler interfacial behavior, was investigated with scanning electron microscopy microstructural analysis. Six concrete mixes containing 0–1.25% fibers with a length of 20 mm were made for ordinary Portland cement (OPC). Further, six concrete mixes with the same fiber content were cast, where 20% POFA substituted OPC. It was found that the incorporation of waste carpet fibers and POFA decreased the workability of concrete. The experimental results revealed that the incorporation of 16% POFA and 0.5% PP waste carpet fibers enhanced the long-term compressive and tensile strength of water-cured specimens up to 20%. The positive interaction amongst POFA and waste carpet fibers subsequently reduced the crack formation and spalling, and reduction in strength loss of the concrete specimens exposed to acid and sulfate solutions. The findings of the study demonstrated that the utilization of PP waste carpet fibers along with POFA in the production of a new alternative concrete composite exposed to corrosive solutions is viable technically and environmentally. Graphical abstract: Image Highlights: Both waste carpet fiber and POFA were used in the production of sustainable concrete. Carpet fiber notably improved the concrete resistance against aggressive environments. The incorporation of carpet fiber and POFA resulted in the reduction of crack formation and spalling. The potential benefits of the wastes in terms of cleaner production are presented.